2020
DOI: 10.4025/actascianimsci.v42i1.47960
|View full text |Cite
|
Sign up to set email alerts
|

Economic feasibility of probiotic use in the diet of Nile tilapia, Oreochromis niloticus, during the reproductive period

Abstract: This work examines the economic advantages of probiotic use in the diet of Nile tilapia broodstock during the reproductive period. For this purpose, Bacillus subtilis was applied as a feed additive. The experimental design was completely randomized with three treatment groups: the T0 control (without probiotic), the T1 continuous probiotic intake, and the T2 alternate probiotic intake at a dose of 0.50 g kg-1 of feed (1010 CFU g-1) with four replicates. For the reproduction assay, 118 females and 48 males of N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…Comparable results were also reported by Ghazalah et al, 363 when probiotic (two commercial probiotics Premalac and Biogen) addition was evaluated in Nile tilapia (1 g), and by Dias et al 364 in juvenile matrinxã, Brycon amazonicus . Recently Dias et al 365 also evaluated the economics of commercial probiotic ( B. subtilis with 10 10 CFU g −1 ) application in the diets of broodstock Nile tilapia, and based upon reproductive indices, they concluded that continuous intake of 0.5 g⋅kg −1 dietary probiotic (10 10 CFU g −1 ) throughout the breeding period of Nile tilapia is economically feasible and cost‐effective due to benefits in reproductive indexes and profitability. For the economic feasibility evaluation of this study, the local (São Paulo, Brazil) price of the feed and the probiotic were considered which corresponded to $ 0.56 (US) and $ 60.00 (US) per kilogram, respectively.…”
Section: Economic Evaluation Of Fufa: Is It Economic or Just Ecologic...mentioning
confidence: 99%
“…Comparable results were also reported by Ghazalah et al, 363 when probiotic (two commercial probiotics Premalac and Biogen) addition was evaluated in Nile tilapia (1 g), and by Dias et al 364 in juvenile matrinxã, Brycon amazonicus . Recently Dias et al 365 also evaluated the economics of commercial probiotic ( B. subtilis with 10 10 CFU g −1 ) application in the diets of broodstock Nile tilapia, and based upon reproductive indices, they concluded that continuous intake of 0.5 g⋅kg −1 dietary probiotic (10 10 CFU g −1 ) throughout the breeding period of Nile tilapia is economically feasible and cost‐effective due to benefits in reproductive indexes and profitability. For the economic feasibility evaluation of this study, the local (São Paulo, Brazil) price of the feed and the probiotic were considered which corresponded to $ 0.56 (US) and $ 60.00 (US) per kilogram, respectively.…”
Section: Economic Evaluation Of Fufa: Is It Economic or Just Ecologic...mentioning
confidence: 99%
“…However, the result of a higher survival rate contributed to a 44% reduction in unit production costs [297]. Studies on the feasibility of synbiotics in aquaculture have consistently shown improvement in economic efficiency compared with control diets, especially when aquatic animals have been under stress conditions such as high stocking density [298] or during the reproductive period [299].…”
Section: Limitations Of the Use Of Synbiotic Agents In Aquaculturementioning
confidence: 99%
“…In tilapia culture, the most commonly used probiotics belong to the genus Bacillus [172]. They are followed, to a lesser extent, by lactic acid bacteria (LABs) [173,174]. The frequent use of Bacillus spp.…”
Section: Probiotics In Tilapia Culturementioning
confidence: 99%